Twin Peak Quasi‐Periodic Oscillations and Stability via Thin‐Shell Formalism of Traversable Wormholes in Symmetric Teleparallel Gravity. Issue 9 (1st August 2022) - Mustafa, G.; Gao, X.; Javed, Faisal
Abstract: This article explores the wormhole geometry in the background of symmetric teleparallel gravity or f ( Q ) $f(\mathcal {Q})$ gravity, where Q $\mathcal {Q}$ is the non‐metricity term, and definite subject for the gravitational interaction. All the energy conditions are investigated for two different generic shape functions. The presence of exotic matter is confirmed due to the violation of the energy conditions. The epicyclic orbits of test particles around wormhole throat for the considered models are discussed. Twin peak Quasi‐periodic oscillations are calculated and presented with the required behavior. We also explore the physical characteristics and stable configuration of thin‐shell developed from the matching of inner obtained solution of wormhole geometry and outer black hole solution in f ( Q ) $f(\mathcal {Q})$ gravity. The stability of shell is discussed by using the speed of sound parameter for both choices of shape functions, i.e., β 1 ( D ) $β _1(D)$ and β 2 ( D ) $β _2(D)$ . It is found that the position of event horizon does not change for different values of the physical parameter for the choice of β 1 ( D ) $β _1(D)$ while it changes for β 2 ( D ) $β _2(D)$ . We explore the proper length, shell energy and entropy of the developed structure for different values of physical parameters. Abstract : This article explores the wormhole geometry in the background of symmetric teleparallel gravity or f (Q) gravity, where Q is the non‐metricity term, and definite subject for the gravitational interaction. All the energy conditions are investigated for two different generic shape functions. The presence of exotic matter is confirmed due to the violation of the energy conditions. The epicyclic orbits of test particles around wormhole throat for the considered models are discussed. Twin peak Quasi‐periodic oscillations are calculated and presented with the required behavior. The authors also explore the physical characteristics and stable configuration of thin‐shell developed from the matching of inner obtained solution of wormhole geometry and outer black hole solution in f (Q) gravity. The stability of shell is discussed by using the speed of sound parameter for both choices of shape functions, i.e., β1 (D) and β2 (D)It is found that the position of event horizon does not change for different values of the physical parameter for the choice of β1 (D) while it changes for β2 (D). The authors explore the proper length, shell energy and entropy of the developed structure for different values of physical parameters.